The influence of grammatical gender on cognition: the case of German and Farsi - Fatemi, Maryam; Mertins, Barbara; Schroeder, Vincent (Technische Universität Dortmund, 2025)
This study investigates whether and how grammatical gender influences cognition by comparing speakers of German, a language with three grammatical genders (masculine, feminine, neutral), and Farsi, a genderless language. Using object description tasks, we examined how grammatical gender affects the assignment of descriptive properties to objects. German monolinguals demonstrated significant effects of grammatical gender on object categorization. This effect was particularly evident in the first adjectives produced, indicating an immediate and automatic link between grammatical gender and conceptual representation. In contrast, Farsi monolinguals showed no such effects, consistent with Farsi’s lack of grammatical gender, and their adjective choices were unaffected by gender category, adjective order, sex, or age. Notably, German speakers perceived objects with neutral grammatical gender as genuinely neutral, underscoring the cognitive reality of the neuter category. These findings highlight how the presence or absence of grammatical gender in a language shapes cognitive processing and support linguistic relativity. The study also emphasizes the importance of including neutral gender and of cross-linguistic comparisons in future research to deepen our understanding of language–thought interactions.
Open linguistics; 11(1)
Keywords: grammatical gender; cognition; conceptual representation; linguistic relativity; 400